Experimental investigation on sugarcane powder filled glass fiber epoxy composite. (2020) - Reddy, A. Vinay; Bharathiraja, G.; Jayakumar, V.
Abstract: Nowadays the natural filler usage is increasing in polymer composites due to environmental concern. The natural fillers are abundantly available in India. Sugarcane is the major crop cultivated in India. Bagasse is the fibrous pulpy residue obtained after sugarcane crushed in mill. It is used for biofuel production and other applications. In this work, sugarcane powder obtained from bagasse was reinforced with randomly oriented short glass fiber in epoxy material. The epoxy composites were fabricated by hand lay-up method. The composites were prepared with 10%, 15%, 20%, 25%, 30% volume fraction sugarcane powder with 20% glass fiber. The mechanical properties such as tensile, flexural and impact strength were investigated as per ASTM standard. Test results show that the 20% glass with 25% sugarcane powder composite exhibited improved mechanical properties.